Uncovering Instructional Media Choices: Teachers Preferences and Shaping Factors - Etika Dewi Kusumaningtyas; Endang Susilowati; Eka fanti Sulistiyaningsih; Salva Andriyani (English Education and Literature Journal (E-Jou), 2026)
Process of implementing instruction media, teachers consider design of classroom activity and instruction that is related to instructional media used. Arrangement of scheming content and instructional media build a noble atmosphere of effective learning. This research aimed to explore teacher preferences of instructional media and its shaping factors. This research was conducted at one of vocational school and addressed to 20 teachers as subject. This research portrayed based on open- ended questionnaires that found text media that is used by the teachers are hand out books or other reference books. Two subjects that employed visual media utilize graphic and picture. Motion media that is employed by teachers is video. Computer- based media as the most employing media of teacher assisted teacher and student to get information. Open educational resources are employed by teachers to get learning material. Moreover, teachers occupied Artificial Intelligence as a medium in the learning process such as canva, quizzizz, Kahoot and quizwhizzee. Audio media and real objects are rarely used by teachers. Moreover, the picture showed that the most occupied media is computer based media. Teachers utilized it since they intended to provide an innovative, attractive and effective learning process. 15% of our subjects utilized Artificial intelligence (AI). Twenty subjects of this study employed digital tools or digital instructional media and integrated digital technology or Artificial Intelligent (AI). The teacher approved that digital and digital tech instructional design boost effective learning process and evaluate the learning outcome effortlessly